1989
DOI: 10.1289/ehp.8982249
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic and spectrophotometric characterization of adducts formed during the reaction of trans,trans-muconaldehyde with 14C-deoxyguanosine 5'-phosphate.

Abstract: Mice liver microsomes oxidatively open the benzene ring to form trans,trans-muconaldehyde, a hematotoxic unsaturated aldehyde. In the present studies, 4.5 imole trans,trans-muconaldehyde was reacted with "4C-2'deoxyguanosine 5'-phosphate in phosphate buffer. Products were separated by high performance liquid chromatography (HPLC). Absorbance was monitored using a diode array detector, and aliquots of the HPLC eluant were collected for UV spectrophotometric analysis and scintillation counting. Under these condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 5 publications
(3 reference statements)
2
9
0
Order By: Relevance
“…The reactions were monitored by HPLC. Within a few hours several small peaks appeared and additional peaks appeared over the course of several days, several of which had UV spectra similar to those reported by Latriano et al 17 ESI-MS of the early mixtures showed the presence of species containing dGuo and muconaldehyde in a 1:1 ratio with and without loss of water; 2:1 species from which 0, 1 and 2 water molecules had been lost were also observed. An interpretation of these results is presented in the Discussion section.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The reactions were monitored by HPLC. Within a few hours several small peaks appeared and additional peaks appeared over the course of several days, several of which had UV spectra similar to those reported by Latriano et al 17 ESI-MS of the early mixtures showed the presence of species containing dGuo and muconaldehyde in a 1:1 ratio with and without loss of water; 2:1 species from which 0, 1 and 2 water molecules had been lost were also observed. An interpretation of these results is presented in the Discussion section.…”
Section: Resultssupporting
confidence: 81%
“…Latriano et al demonstrated that the reaction of E,E -muconaldehyde with 14 C-labeled dGuo-5´-phosphate in phosphate buffer, pH 7.4 yielded several radioactive products of unknown structure. 17 …”
Section: Introductionmentioning
confidence: 99%
“…Well-resolved minor peaks were detected at retention times of 2.8, 9.9, and 20.2 min, and a group of six peaks eluted between 5.6 and 8.7 min. These results are similar to those obtained in collaborative work with Latriano et al (26) who used radiolabeled deoxyguanosine 5'-phosphate in the reaction with TTM. Alpha,betaunsaturated aldehydes have been reported to react with deoxyguanosine, forming products with one additional ring involving the N-1 position and the amino group on C-2 (27,28).…”
Section: Genotoxicity Of Ttmsupporting
confidence: 90%
“…9 Reactions of (2,Z)-muconaldehyde with nucleosides provides a basis for understanding the molecular mechanism of mutagenesis by this aldehyde. In a previous study (27) @,E)-muconaldehyde was reacted with [Wdeoxyguanosine 5'-phosphate, but the structures of products observed chromatographically were not determined. We have found that reaction of (2,Z)-muconaldehyde with 2,3,5-tri-O-acetylguanosine gives adduct Sa, the structure of which was assigned by analogy to 7.…”
Section: Discussionmentioning
confidence: 95%